A study of generation Y travel behaviour in Malaysia - Tan, Lay Yen (2015)
Generation Y is a special and creative group. They grew up in the wealthier environment and they tend to enjoy the life. This group includes several age cohorts which includes the teens and also young adults. They are the first generation who grew up with the environment full of new technology. There are the pull and push factors that are related to their motives for travelling and also may affect their travel behaviour. However, there is not much research mentioned about Generation Y travel motivation and travel behaviour during the trip. This study will study on the travel behaviour pattern of Malaysian Generation Y. To achieve the aim of this study, push and pull factors of travel motivation were used to identify the travel motivation of Generation Y. Then the travel behaviour of Generation Y during the trip was also to be determined through quantitative methods. Then only the travel behaviour pattern of Generation Y was been identified based on the motivation and behaviour. The results show that most of the Generation Y tends to travel because of knowledge seeking and for relaxation purposes. The results showed that the cost, core attraction and landscape are the main pull factors of travel motivation for Generation Y. The push and pull factor are the first stage in the travel behaviour pattern which Generation Y made their decision to travel. The analysis of travel behaviour of Generation Y also showed that most of Generation Y had a tendency for travelling during semester breaks, staying in hotels, eating local food and travelling with their family and friends for the purpose of relax and exploring new destination. Sightseeing was identified as the most preferred activities by Generation Y and primary source of information in planning their vacation include Internet (Trip Advisor, Groupon and Air Asia) and friends’ recommendations. Therefore, this study showed how the travel behaviour pattern of Generation Y in Malaysia by determine the push and pull factors of travel motivation in making their decision to travel and also the travel behaviour during the trips.